Factors Affecting the Price of Local Siamese Oranges at the Retailer Level in Baturaja City, Ogan Komering Ulu Regency - zelfan ariesko; Henny Rosmawati; Putri Ayu Ogari (Jurnal Ilmiah Mahasiswa AGROINFO GALUH, 2026)
This study aimed to analyze the influence of supply volume, demand, prices of other oranges, farm-gate prices, transportation costs, fruit quality, and harvest season on the price of local Siamese oranges at the retailer level in Baturaja City, Ogan Komering Ulu Regency. A quantitative approach was applied using a survey method with 30 randomly selected orange retailers. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that all independent variables simultaneously had a significant effect on the retail price of Siamese oranges, with a significance value of 0.000 (< 0.05) and a coefficient of determination (R²) of 0.831. Partially, each variable—supply volume, demand, other orange prices, farm-gate prices, transportation, quality, and harvest season—had a statistically significant effect at the 5% or 10% confidence level. These findings indicated that these factors played an essential role in determining the retail price of Siamese oranges and should be considered in price management strategies. This study provided practical insights for retailers, farmers, and policymakers in developing more efficient pricing and distribution strategies for local citrus products. Keywords: orange price, retailers, supply, demand, quality, multiple regression